Memorandum on times of waking patients in hospitals - Hastings, Somerville, 1878-1967 (1931)
1931 1931 1930s 2 pages PRIVATE & CONFIDENTIAL MEMORANDUM ON TIMES OF WAKING PATIENTS IN HOSPITAL. by SOMERVILLE HASTINGS, M.P. Sick persons need much sleep and generally speaking the more sleep they can get the better for them. Patients who are nursed at home or who have a room to themselves usually drop off for a short sleep several times during the day, but in a hospital ward where there is something going on almost the whole day, this is more difficult. Besides this, watching the general activities of the ward, which patients generally find on the whole interesting and which makes a spell of sickness spent in a hospital ward much less boring than one in a single room, is at the same time apt to be fatiguing, so that a longer time of undisturbed quiet is necessary at night. In most hospitals patients are awakened early. In a good many they are washed at 5 a.m. ; in a few even before this hour. There are very few hospitals in England in which the patients are allowed to sleep after 6 a.m. The reason for this practice is to be found in the fact that the hospitals of Britain have been evolved as charitable institutions for the sick poor and that the demand has always exceeded the supply. In consequence hospitals have had be run as economically as possible. By beginning the important period of washing and bedmaking very early in the morning a smaller staff of nurses has been made possible. The fashion having once been set in the voluntary hospitals, the nursing profession, the most conservative of all, has insisted on the same procedure in the municipal and other hospitals. That this explanation is the correct one is shown by the fact that in nursing homes patients are awakened at much more reasonable hours. The practice being established in this way the hospital authorities have been hard put to to try and justify it. They have pointed out that if all work is completed by 8 p.m. and the ward is quiet, 9 hours sleep is possible before 5 a.m. This is of course true, but unfortunately the wards are by no means always quiet by 8 p.m. The house surgeon or other medical officer usually makes a round at 9 or 9.30 p.m., and is liable to disturb patients. Moreover, many of our hospitals are situated in busy parts of towns and the streets do not often become quiet till 11 or 12 p.m. or later still. Further, not a few patients after a restless night, drop off to sleep after 2 a.m. and for these an awakening at 5 a.m. is most undesirable for only the very best sleepers can fail to be disturbed by the general turmoil necessitated in washing and bedmaking. It is also urged that most hospital patients are used to getting up at 5 a.m. or before and therefore, have formed the habit of waking at this hour. In the case of chimney sweeps and lamplighters this is probably correct but it may be pointed out that manual workers start work much later than was the practice some 30 or 40 years ago, and that all classes now make use of the hospitals. 292/842/1/6